Improving quality of strawberry by novel essential oil nanoemulsions of Echinophora platyloba combined with Aloe vera gel and gum arabic - Iman Kebriti; Mousa Solgi; Mohammad Velashjerdi (Scientific Reports)
Abstract Strawberry fruits are highly perishable and have a limited shelf life. Therefore, effective methods such as essential oils (EOs) and edible coatings are required to mitigate spoilage and maintain fruit quality during storage. In the current study, Echinophora platyloba EO was extracted and subsequently formulated into a nanoemulsion. The strawberries were then coated using an immersion method with the prepared nanoemulsions, gum Arabic (GA), and Aloe vera gel (AV). The coating treatments included: distilled water control, 5% GA, 20% AV, 0.5% E. platyloba essential oil, 5% GA + 0.5% E. platyloba nanoemulsion essential oil, and 20% AV + 0.5% E. platyloba nanoemulsion EO. The quality of strawberries was assessed over a storage period of 3, 6, 9, 12, and 15 days. The results revealed that the EO nanoemulsion in combination with GA and AV gel coatings provided superior preservation compared to the control and single-component treatments (pure EO, GA, or AV gel). Coatings with 5% GA + 0.5% EO nanoemulsion and 20% AV + 0.5% EO nanoemulsion demonstrated the highest firmness while achieving the lowest weight loss, titratable acidity (TA), total soluble solids (TSS), TSS/TA ratio, decay percentage, and tissue browning at the end of the storage period. Notably, the decay index in the 20% AV + 0.5% EO nanoemulsion treatment was 17% lower than the 5% GA + 0.5% EO nanoemulsion treatment and 75% lower than other treatments after the experiment. These coatings are recommended due to their eco-friendly, biodegradable nature and cost-effectiveness, making them a promising solution for enhancing the shelf life and quality of strawberries.